2020
DOI: 10.1039/c9cp06102a
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition mechanism scenarios of CL-20 co-crystals revealed by ReaxFF molecular dynamics: similarities and differences

Abstract: Overall scenarios first revealed clearly by ReaxFF MD for self-heating, similar product distributions and altered kinetics in the three-stage decomposition of CL-20 and its cocrystals under adiabatic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 62 publications
4
42
0
Order By: Relevance
“…To summarize, due to its molecular structure that is liable to deform under EF, CL-20 is more sensitive to EF than HMX. 16 and our results agree well with this trend.…”
Section: Electric Field Effect In Evolution Of Bond Lengthsupporting
confidence: 92%
See 3 more Smart Citations
“…To summarize, due to its molecular structure that is liable to deform under EF, CL-20 is more sensitive to EF than HMX. 16 and our results agree well with this trend.…”
Section: Electric Field Effect In Evolution Of Bond Lengthsupporting
confidence: 92%
“…This can be attributed to the molecular stability of HMX with a higher decomposition barrier than that of CL-20 as mentioned above. Moreover, it is found that the decomposition temperature of HMX is about the same ($1200 K) for both CEF and OEF, and close to that of thermal decomposition, 16 indicating that the decomposition of the HMX depends mostly on temperature rather than the heating process of the molecules. We find that the decomposition of CL-20 in CL-20/HMX cocrystal is significantly slower than that in pure CL-20 (CL-20/HMX cocrystal removing HMX molecules is viewed as pure CL-20) as shown in Figure 4A.…”
Section: Electric Field Effect In Evolution Of Chemical Speciesmentioning
confidence: 67%
See 2 more Smart Citations
“…The quantum chemistry calculation by the simulation method of ReaxFF-MD was in good consistence with corresponding experimental results. This method was widely used in various reaction systems, such as the thermal decomposition of fossil fuels, the oxidation or combustion processes of alkanes and hydrocarbons, and the explosion of energetic materials [17,[22][23][24]. The bond formation and breakage in the molecular dynamic simulation was described by ReaxFF, a reactive force field based on the bond order firstly proposed by van Duin [25,26].…”
Section: Reaxff MD Simulationsmentioning
confidence: 99%